Enhancing Students’ Understanding of Operation in Integers through Joyful Learning with GeoGebra™ Applet - Sanni Merdekawati (Southeast Asian Mathematics Education Journal, 2022)
This paper demonstrates a teacher-as-researcher intervention study by utilizing GeoGebra™ activities in the teaching and learning of arithmetical operations with integers. The researcher evaluated how the applet can elevate students understanding of the concepts of arithmetic integer operations. The data was collected through recordings of students’ worksheets and communications in a virtual classroom. The teacher monitored students’ progress and provided immediate suggestions and assistance via several methods. As a result, students could communicate and interact with each other and the teacher through the applet. Students were working on online activities as it happened during the COVID-19 pandemic period. A joyful and meaningful context was implemented in the lessons. The results were tremendously significant and hopefully will inspire readers and teachers.